Improved Ability To Identify Ideas Of Persuasive Speech Text By Using Media Of Ideas Card In Class Ix Junior High School 2 One Roof Ulu Moro’o School - Viktiar Gulo (EDUCATION JOURNAL OF INDONESIA, 2020)
This study aims to determine the increase in the ability to identify ideas of persuasive speech text of class IX students of SMP Negeri 2 Satu Atap Ulu Moro'o in the 2020/2021 academic year using the Idea Card Learning Media. The subjects of this study were students of class IX SMP Negeri 2 Satu Atap Ulu Moro'o, totaling 20 students. This research was conducted in the odd semester of the 2020/2021 learning year. The method used in this research is a classroom action research design. The action is carried out in 2 cycles, namely Cycle I and Cycle II. Each cycle consists of four stages, namely planning, implementing the action, observing, and reflecting. Data analysis was performed using quantitative and qualitative data analysis techniques. The results of this study indicate an increase in learning outcomes in pre-cycle, Cycle I, and Cycle II. The students' ability in identifying persuasive speech text ideas increased from pre-cycle to cycle I and from cycle I to cycle II. The average value in the pre-cycle was 65.5 then increased to 73 in Cycle I. While the increase in Cycle II, from Cycle I 73 to 87. The completeness achieved from pre-cycle was 55% to 70% in Cycle I. Then from Cycle I with completeness of 70% to 95% in Cycle II. These results strengthen the evidence that the learning outcomes of grade IX students on the material of identifying persuasive speech text ideas can be improved with the use of Idea Card Learning Media. The average value in the pre-cycle was 65.5 then increased to 73 in Cycle I. While the increase in Cycle II, from Cycle I 73 to 87. The completeness achieved from pre-cycle was 55% to 70% in Cycle I. Then from Cycle I with completeness of 70% to 95% in Cycle II. These results strengthen the evidence that the learning outcomes of grade IX students on the material of identifying persuasive speech text ideas can be improved with the use of Idea Card Learning Media. The average value in the pre-cycle was 65.5 then increased to 73 in Cycle I. While the increase in Cycle II, from Cycle I 73 to 87. The completeness achieved from pre-cycle was 55% to 70% in Cycle I. Then from Cycle I with completeness of 70% to 95% in Cycle II. These results strengthen the evidence that the learning outcomes of grade IX students on the material of identifying persuasive speech text ideas can be improved with the use of Idea Card Learning Media.